Reproductive Health Policies 2017 - United Nations (United Nations, 2018)
Drawing on information published in the World Population Policies Database, this data booklet provides up-to-date information on government policies on reproductive health issues, including access to family planning, policies to promote sexual and reproductive health of adolescents, laws on abortion and programmes to reduce maternal mortality, for all 193 Member States, 2 Observer States and 2 non-member States of the United Nations. The booklet also provides latest estimates of contraceptive use and unmet need, maternal mortality ratio, antenatal care and delivery care, adolescent fertility and other selected indicators. The Population Division of the United Nations Department of Economic and Social Affairs was established to play an active role in the intergovernmental dialogue on population and development, producing constantly updated demographic estimates and projections for all countries, including data essential for the monitoring of development around the world.